The role of BTBD9 in the cerebellum, sleep-like behaviors and the restless legs syndrome - Lyu, Shangru (Neuroscience, 2020)
Recent genome-wide association studies (GWAS) have found cerebellum as a top hit for sleep regulation. Restless legs syndrome (RLS) is a sleep-related sensorimotor disorder characterized by uncomfortable sensations in the extremities, generally at night, which is often relieved by movements. Clinical studies have found that RLS patients have structural and functional abnormalities in the cerebellum. However, whether and how cerebellar pathology contributes to sleep regulation and RLS is not known. GWAS identified polymorphisms in BTBD9 conferring a higher risk of sleep disruption and RLS. Knockout of the BTBD9 homolog in mice (Btbd9) and fly results in motor restlessness and sleep disruption. We performed manganese-enhanced magnetic resonance imaging on the Btbd9 knockout mice and found decreased neural activities in the cerebellum, especially in lobules VIII, X, and the deep cerebellar nuclei. Electrophysiological recording of Purkinje cells (PCs) from Btbd9 knockout mice revealed an increased number of non-tonic PCs. Tonic PCs showed increased spontaneous activity and intrinsic excitability. To further investigate the cerebellar contribution to RLS and sleep-like behaviors, we generated PC-specific Btbd9 knockout mice (Btbd9 pKO) and performed behavioral studies. Btbd9 pKO mice showed significant motor restlessness during the rest phase but not in the active phase. Btbd9 pKO mice also had an increased probability of waking at rest. Unlike the Btbd9 knockout mice, there was no increased thermal sensation in the Btbd9 pKO. Our results indicate that the Btbd9 knockout influences the PC activity; dysfunction in the cerebellum may contribute to the motor restlessness found in the Btbd9 knockout mice.